Diasporic Consciousness in Bharati Gautam’s Vigata Ra Baduli - Timalsina, Ramji (JODEM: Journal of Language and Literature, 2021)
This article aims to explore the diasporic consciousness reflected through Bharati Gautam’s collection of memoirs Vigata Ra Baduli [Past and Hiccups]. As an American Nepali diasporic writer, Gautam has given expression to her experiences in the book. Spending about three and half decades as a diasporan, the writer’s consciousness is different from that of the common Nepali migrants to the USA. To analyse Gautam’s consciousness, this research has used African American philosopher DuBois’s idea of double consciousness. Different interpretations of DuBoisian double consciousness agree that a diasporan has a specific transnational awareness. The elemental aspects of such awareness are the dual nature of thought, relationship to the memory of the homeland, confused state of mind, alienation, a sense of loss of history and culture along with the gain of new cosmopolitan identity. The analysis concludes that Gautam’s diasporic consciousness is expressed through her conscious dealing with diasporic distance, marginalization and discrimination in both the homeland and hostland, the realization of her own divided self, feeling of alienation and the connection with the root. It is hoped that this study will contribute to the discourse of Nepali diasporic consciousness.